Awareness, knowledge, social norms, and vaccination intentions among Khmer mother–daughter pairs. Issue 3 (3rd April 2021) - Lee, Haeok; Kim, Deogwoon; Kiang, Peter Nien-chu; Cooley, Mary E.; Shi, Ling; Thiem, Linda; Kan, PenhSamnang; Chea, Phala; Allison, Jeroan; Kim, Minjin
ABSTRACT: Cervical cancer is caused by human papillomavirus (HPV) infection, which can be prevented by vaccination. Mothers play an important role in promoting vaccination and health education. However, Cambodian American mothers reported to have challenges to play a role as primary health educators due to lack of health knowledge and language and cultural gaps. Therefore, this study aims to understand the Cambodian American daughters' and mothers' awareness, knowledge and social norms of HPV vaccination and their health communication and vaccination decision-making. We conducted a pilot randomized clinical trial to promote HPV vaccination. In this study, we have only reported findings from baseline data examining individual, interpersonal and social determinants of HPV vaccination behavior among 19 dyads of Cambodian American mothers and daughters. Both mothers and daughters demonstrated low levels of awareness and knowledge. A significant relationship was found between the daughters' HPV vaccine decisions and their perception of their mothers' intention on HPV vaccination for them. Culturally and linguistically appropriate communication strategies such as storytelling or visual presentation approaches may be more effective than the current practice of using information-based written materials to promote HPV vaccination and health education among Cambodian Americans.